FUNGSI DAN PERAN KEPEMIMPINAN SEKOLAH DALAM MEMBERIKAN REWARD UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Muhammad Iqbal (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2022)
Reward is an award in the form of reward, gifts, or reward given to a student who has done something good, or has succeeded in reaching a certain stage or development, or has reached a target. Reward as an important tool in education is given to students who have done something good, or havesucceeded in achieving acertain development, or have achieved a target in learning. In the concept of education, reward is a tool in increasing motivation and innovation in students. Awards given by school principals or teachers can motivate and innovate to students to increaase students’ stronger interest in learning. Even if it’s only a gesture of throwing a smile, thumbs up, or a given greeting by school leardership or teacher, it can please the feeling with a happy heart that is manifested in body movements with a happy soul. So reward and interest in learning cannot be separated in educational methods that must be carried out by school leardership or teachers.